The Coziest Place on Earth / Rani Aryani Widjono - Widjono, Rani Aryani (Faculty of Art and Design, 2021)
Remember to take a deep breath, take your time. We are already racing for nothing.Born in Manila, Philippines. Rani Aryani Widjono is a full time interaction design lecturer at UMN. She is an Art & Design enthusiast, ceramicdesigner and Advisor at Nusakara Artspace. Besides teaching, she is also running her own pottery studio, Hellorat Project since 2015.